Compression hosiery to avoid post-thrombotic syndrome (CHAPS) protocol for a randomised controlled trial (ISRCTN73041168). Issue 4 (12th April 2021) - Thapar, Ankur; Lawton, Rebecca; Burgess, Laura; Shalhoub, Joseph; Bradbury, Andrew; Cullum, Nicky; Epstein, David; Gohel, Manjit; Horne, Robert; Hunt, Beverley J; Norrie, John; Davies, A H
Abstract : Introduction: Up to 50% of patients develop post-thrombotic syndrome (PTS) after an above knee deep vein thrombosis (DVT). The aim of the study was to determine the effect of graduated compression stockings in preventing PTS after DVT. Methods and analysis: Pragmatic, UK multicentre randomised trial in adults with first above knee DVT. The standard of care arm is anticoagulation. The intervention arm will receive anticoagulation plus stockings (European class II, 23–32 mm Hg compression) worn for a median of 18 months. The primary endpoint is PTS using the Villalta score. Analysis of this will be through a time to event approach and cumulative incidence at median 6, 12 and 18 months. An ongoing process evaluation will examine factors contributing to adherence to stockings to understand if and how the behavioural interventions were effective. Ethics and dissemination: UK research ethics committee approval (reference 19/LO/1585). Dissemination though the charity Thrombosis UK, the Imperial College London website, peer-reviewed publications and international conferences. Trial registration number: ISRCTN registration number 73041168.